Aplikasi Eletronik Manajemen Keuangan DIPA pada Lembaga Pendidikan Islam Negeri di Tengah Pandemi Covid-19 Sebagai Upaya WFH - Zebua, Ali Marzuki (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2020)
It is inevitable that the influence of the emergence and spread of the Covid-19 pandemic has greatly affected all aspects of life, including in the world of education. This condition ultimately provokes a response from stakeholders and education policymakers by changing the processes and procedures for activities in education. All office and administration activities in education are carried out online. On the other hand, educational institutions are also required to be able to provide standard health services through WFH. In this paper, the author is interested in how the DIPA online financial management application system at State Islamic education institutions in the midst of the Covid-19 pandemic is carried out effectively and efficiently as a form of an effort to work from home (Work From Home ). Policies in financial management during this pandemic are through e-SPM application in applying accounting principles and e-Rekon in applying audit principles. This app is very effective in implementing social distancing health protocols. The effect of this will also be the efficiency of the official travel budgets of State Islamic education institutions. The usefulness of this paper is a form of information for education stakeholders who may not have seen many applications in the management of public education finance.